Cycle ergometer and rebound exercises with chest physiotherapy - a useful adjunct for sputum expectoration in mild to moderately symptomatic hiv infected children. - S.S. Maharaj; P.M. Jeena (AOSIS, 2008)
Background: Sputum expectoration of lung secretionsin HIV  infected children with associated respiratory conditions is oftendifficult. Chest physiotherapy is often recommended to assist in thisprocess but is not always successful. A erobic exercises may have bene-ficial effects on sputum expectoration but its safety is uncertain. Aim: The primary aim of this study was to determine if cycle ergometerand rebound exercises are safe for mild to moderately symptomatic HIV  infected children and if these aerobic exercises followed by chestphysiotherapy could augment sputum expectoration.Method: Thirty six A frican 8-12 year old males performed 15 minutesof either cycle ergometer or rebound exercises. A  modified 6 minutewalking test to ensure fitness of the enrolled subjects prior to randomization was performed. Heart and respiratoryrates, blood pressure and oxygen saturation was monitored for safety. Sputum expectorated was measured in a calibratedvial at baseline, 5, 10, and 15 minutes post exercise followed by 30 minutes of conventional chest physiotherapy. R esults: Total sputum produced during and post rebounding exercise was significantly higher than cycle ergometerexercises (12.6 vs. 9.8mls p=0.0002). The quantity of sputum obtained over each time point after rebound exercise wassignificantly more than cycle ergometer (5, 10 & 15 minutes; p=0.0084, p= 0.0002, p=0.0002 respectively). There wereno significant differences in heart and respiratory rates, blood pressure and oxygen saturation of enrolled subjectsbetween these exercises and no cases reached the threshold for stopping the exercise.Conclusion: Cycle ergometer and rebound exercises are safe for mild to moderately symptomatic HIV  infected children. Rebound exercises followed by chest physiotherapy can be used as a safe adjunct to significantly increasesputum expectoration.